Alveolar adenoma and coexisting atypical adenomatous hyperplasia: a case report and literature review - Lu, Yen-Wen; Chang, Shih-Lung; Yeh, Yi-Chen; Hsieh, Yei-San (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
Alveolar adenoma is a rare tumour of the lung. It is typically found in asymptomatic adults as a peripheral or subplerual nodule on imaging examination. Microscopically, the tumour is composed of admixture of epithelial and mesenchymal component in variable sized cystic or alveolar structures. The tumour shows a benign nature. There have been no reported recurrences or metastases. Malignant transformation of alveolar adenoma and coexisting with lung carcinoma have been rarely described. In this article, we report a case of an alveolar adenoma and coexisting atypical adenomatous hyperplasia. This case, contributing to the limited numbers of cases described to date, illustrates the importance of awareness on the possibility of alveolar adenoma being associated with lung carcinoma and its precursor lesions especially when diagnosed by small biopsy specimens.